English for Academic CVs, Resumes, and Online Profiles - Wallwork, Adrian (English for Academic Research, 2019)
Are you a graduate, postgraduate or PhD student? Building a CV or profile can be difficult for anyone, but especially for those whose first language is not English. This book is essential for those looking to promote themselves in the academic community, and can be used both for self-study, as well as in an English for Academic Purposes (EAP) course. The book contains tips, do's and dont's, and discussion points that can be used by instructors. Based on interviews with recruiters and an analysis of hundreds of CVs from around 40 different countries, the book is structured as a series of FAQs. Topics covered include: how recruiters and HR people analyse a CV whether using a template is a good idea how to present your personal details and whether to include a photo how to write an Objective and a personal profile what to write in each section (Education, Work Experience, Skills, Personal Interests) how tohighlight your language, communication and team skills how to get and write references The last chapter of the book contains a simple template to help you get the job of your dreams! Other books in this series include: English for Writing Research Papers English for Research: Usage, Style, and Grammar English for Presentations at International Conferences English for Academic Research: Grammar / Vocabulary / Writing Exercises English for Academic Correspondence English for Interacting on Campus Adrian Wallwork is the author of over 40 books aimed at helping non-native English speakers to communicate more effectively in English. He has published with SpringerNature, Oxford University Press, Cambridge University Press, Scholastic, BEP and the BBC.